Influence of Social Media Marketing, Product Quality, and Brand Image On Customer Loyalty Through Customer Satisfaction (Study on La Moringa Consumers, NTT) - Muh K Bonesaputra Rukman; Heri Praktikto; Wening Patmi Rahayu (Brilliant International Journal Of Management And Tourism, 2023)
The purpose of this study was to determine the effect of Social Media Marketing, Product Quality, and Brand Image on Customer Loyalty through Customer Satisfaction on La Moringa NTT consumers. quantitative research using descriptive and explanatory research methods, for data processing using SEM-PLS. Survey data was collected online and it was found that 217 respondents were La Moringa consumers. Social Media Marketing, Product Quality, and Brand Image have a positive and significant effect on Customer Satisfaction, H1, H2 and H3 are accepted. Social Media Marketing, Product Quality, and Brand Image have a direct positive and significant effect on Customer loyalty, Customer Satisfaction has a positive and significant effect on Customer loyalty H4, H5, H6, and H7 are accepted. Whereas Customer Satisfaction has a positive and significant effect on mediating Social Media Marketing, Product Quality, and Brand Image on Customer Loyalty, H8, H9, and H10 as mediating variables are accepted